2022
DOI: 10.3390/cells11203274
|View full text |Cite
|
Sign up to set email alerts
|

TRAF3/p38-JNK Signalling Crosstalk with Intracellular-TRAIL/Caspase-10-Induced Apoptosis Accelerates ROS-Driven Cancer Cell-Specific Death by CD40

Abstract: The capacity to induce tumour-cell specific apoptosis represents the most unique feature of the TNF receptor (TNFR) family member CD40. Recent studies on the signalling events triggered by its membrane-presented ligand CD40L (mCD40L) in normal and malignant epithelial cells have started to unravel an exquisite context and cell type specificity for the functional effects of CD40. Here, we demonstrate that, in comparison to other carcinomas, mCD40L triggered strikingly more rapid apoptosis in colorectal carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…MMP13 contributes to the proliferation, migration, and anchorage-independent clonogenicity of mouse mammary tumorigenic cell lines ( 29 ). The tumor necrosis factor receptor family member CD40 is critical for the immune system and induces tumor cell-specific apoptosis ( 30 ). However, how the regulation of BCL2 , MMP11 , MMP13 , and CD40 mediated by SOCS3 overexpression affects lipid metabolism and the complex relationship between cell survival and lipid metabolism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…MMP13 contributes to the proliferation, migration, and anchorage-independent clonogenicity of mouse mammary tumorigenic cell lines ( 29 ). The tumor necrosis factor receptor family member CD40 is critical for the immune system and induces tumor cell-specific apoptosis ( 30 ). However, how the regulation of BCL2 , MMP11 , MMP13 , and CD40 mediated by SOCS3 overexpression affects lipid metabolism and the complex relationship between cell survival and lipid metabolism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then rinsed twice in PBS +1% FBS buffer. For surface protein expression, immunolabelled cells were acquired on a Guava EasyCyte 5 flow cytometer and data analyzed using EasyCyte software (Millipore, Watford, United Kingdom) as previously (Ibraheem et al, 2022).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Quantitative protein detection was performed by immunoblotting as detailed elsewhere (Ibraheem et al, 2022). Briefly, cell cultures were lysed and lysates established using an SDS-based buffer (Georgopoulos et al, 2014) containing 2 mg/mL DTT and 1% (v/v) protease inhibitor cocktail set 3 (Calbiochem, supplied my Merck).…”
Section: Western Blottingmentioning
confidence: 99%
“…Although this phosphorylation protects Bid from cleavage by caspase-8, it allows a more profound cleavage of Bid to jBid to promote apoptosis. Furthermore, JNK can also induce TRAIL to initiate either caspase-10-associated, or tBid-activated mitochondrialinduced apoptosis [115]. Furthermore, it was shown that JNK can translocate to the mitochondria in response to TNF, where it interacts with Sh3BP5 at the mitochondrial membrane [116].…”
Section: Jnk In the Induction And Regulation Of Apoptosismentioning
confidence: 99%